Spatial analysis of milk and cottage cheese reveals poor microbial quality and contamination with foodborne pathogens in the central highlands of Ethiopia - Keba, Abdi; Girmay, Gebrerufael; Nahusenay, Henok; Zewdu, Ashagrie (Frontiers in Sustainable Food Systems, 2025)
IntroductionFoodborne diseases that result from a wide range of illnesses caused by contaminated foods remain a challenge in least-developed countries. The objective of this study was to evaluate microbial quality and safety of milk and cottage cheese and spatial distribution of microbial quality indicators and foodborne pathogens along the dairy value chain in the three regions of the country.MethodsA cross-sectional study was conducted from December 2020 to May 2021. A total of 912 samples were collected and tested for aerobic plate count, total coliform count, Escherichia coli count, Listeria monocytogenes, Salmonella enterica, and Campylobacter spp., according to standard methods of microbial enumerations and isolation procedures.ResultsMicrobial quality of milk and cottage cheese in the dairy value chain was found poor quality, as the total bacteria count, total coliform count, and Escherichia coli count were estimated to be 98% (95% CI 97.2–98.9%), 61.2% (95% CI 58–64.3%), and 28.6% (95% CI 25.8–31.6%), respectively. Microbial load of milk and cottage cheese samples exceeded the limits set by the Ethiopian Standards Agency. The overall prevalence of samples contaminated by at least one pathogen was 50.3% (95% CI 47.1–53.7%), indicating that raw milk samples collected from milk collectors were predominantly contaminated (OR = 2.1, p = 0.003), followed by milk processors (OR = 1.3, p = 0.003).DiscussionThe spatial analysis revealls that the poor microbial quality standards and distribution of microbial quality indicators and foodborne pathogens were concentrated in the central highlands of Ethiopia, within nearly 100 kilometers radius from Addis Ababa city to surrounding towns. This study offers some insight into the importance of food traceability to prevent food safety threats along the dairy value chain and intervention areas.